SOME ISSUES OF THE SOVIET NATIONAL PRESS FORMATION IN AUTONOMIES OF THE NORTHERN CAUCASUS IN THE 1920S’ - Gapeeva, Marina Sergeevna (History, Archeology and Ethnography of the Caucasus, 2019)
The article discusses the formation and development of the Soviet national press in the autonomies of the North Caucasus in the first post-revolutionary decade. The national press became one of the primary tasks in building socialist culture and socialist ideology. The article reflects the role of the media as a tool for the formation of public consciousness and the most powerful method of mass education and the fight against illiteracy. The process of Latinization of the alphabets of mountaineers is considered, the reasons for this process are explained, the advantages of national alphabets on a Latin graphic basis are revealed as compared to the majority of the highlanders, using the Arab one. The author notes that Latinization was a kind of catalyst for the development of the print. The range of issues that the first Soviet newspapers were supposed to cover as ideas and principles of the Soviet state is defined. The article describes the structure of an extensive media system aimed at all sectors of society. There are groups of newspapers of regional significance, published in Russian, as well as newspapers, published in the local languages of the mountaineers. The role of local newspapers in the process of emergence and development of national artistic culture is shown. The first newspapers became the focus of the development of the national literature of the highlanders, since it was on the pages of the newspapers that the representatives of the mountain national artistic intelligentsia published their first works. The process of creating associations of proletarian writers, which took place by rallying local authors of the artistic word around major printed publications of the region, is revealed.
Keywords: North Caucasus; autonomies; national press; mass media; romanization of alphabets; artistic culture; association of proletarian writers.